Gas Chromatography-Mass Spectrometry Analysis and α-Glucosidase Inhibitory Activity of n-Hexane Extract of Bilajang Bulu (Merremia Vitifolia) Leaves - Candra Yulius Tahya; Karnelasatri Karnelasatri (Department of Chemistry Faculty of Science and Technology Walisongo, 2021)
One of the most effective treatments for diabetes mellitus is to inhibit α-glucosidase, which inhibits glucose absorption by the epithelium membrane of the small intestine. In South Sulawesi, Indonesia, Merremia vitifolia is used as a traditional medicine for the treatment of diabetes. The aims of this study are to (1) assess the extract's ability to inhibit α - glucosidase and (2) identify volatile organic compounds in n-hexane of Merremia vitifolia extract. Extraction was conducted by maceration. The inhibitory activity of quercetin towards α-glucosidase has the IC50 = 2.53 ± 0.16 µg/mL, and by n-Hexane extract of Merremia vitifolia leaves has the IC50 = 14.4 ± 1.52 µg/mL. Then, n-Hexane extract of Merremia vitifolia leaves has strong α-glucosidase inhibitory activity. The compounds that have been identified based on Gas Chromatography-Mass Spectrometry (GC-MS) analysis with similarity index ≥ 89% which are caryophyllene (0.94%), (E)-β-famesene (4.72%), neophytadiene (9.78%), phytol (65.94%), 9,12,15-octadecatrienoic acid (6.71%), 1,5-cyclodecadiene (6.76%), squalene (4.48%), stigmasterol (4.08%), γ-sitosterol (10.20%), Serratol (23.12%), vitamin E (2.78%) and lup-20(29)-en-3-one (21.04%). Based on a literature study, the presence of phytol, neophytadiene, β-caryophyllene, stigmasterol, γ-sitosterol, and lup-20(29)-en-3-one have contributed to the strong α-glucosidase inhibitory activity of n-Hexane extract of Merremia vitifolia leaves.